Metallosupramolecular Photonic Elastomers with Self‐Healing Capability and Angle‐Independent Color. Issue 6 (13th December 2018) - Tan, Haiying; Lyu, Quanqian; Xie, Zhanjun; Li, Miaomiao; Wang, Kui; Wang, Ke; Xiong, Bijin; Zhang, Lianbin; Zhu, Jintao
Abstract: Photonic elastomers that can change colors like a chameleon have shown great promise in various applications. However, it still remains a challenge to produce artificial photonic elastomers with desired optical and mechanical properties. Here, the generation of metallosupramolecular polymer‐based photonic elastomers with tunable mechanical strength, angle‐independent structural color, and self‐healing capability is reported. The photonic elastomers are prepared by incorporating isotropically arranged monodispersed SiO2 nanoparticles within a supramolecular elastomeric matrix based on metal coordination interaction between amino‐terminated poly(dimethylsiloxane) and cerium trichloride. The photonic elastomers exhibit angle‐independent structural colors, while Young's modulus and elongation at break of the as‐formed photonic elastomers reach 0.24 MPa and 150%, respectively. The superior elasticity of photonic elastomers enables their chameleon‐skin‐like mechanochromic capability. Moreover, the photonic elastomers are capable of healing scratches or cuts to ensure sustainable optical and mechanical properties, which is crucial to their applications in wearable devices, optical coating, and visualized force sensing. Abstract : Photonic elastomers with self‐healing capability and angle‐independent color are fabricated through the combination of a supramolecular elastomer with isotropic nanostructures, exhibiting chameleon‐skin‐like mechanochromic capability. Interestingly, the photonic elastomers are capable of healing scratches or cuts, ensuring the optical and mechanical properties.